2011
DOI: 10.3758/s13415-011-0056-8
|View full text |Cite
|
Sign up to set email alerts
|

A habituation account of change detection in same/different judgments

Abstract: We investigated the basis of change detection in a short-term priming task. In two experiments, participants were asked to indicate whether or not a target word was the same as a previously presented cue. Data from an experiment measuring magnetoencephalography failed to find different patterns for "same" and "different" responses, consistent with the claim that both arise from a common neural source, with response magnitude defining the difference between immediate novelty versus familiarity. In a behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

7
1

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 73 publications
(93 reference statements)
0
21
0
Order By: Relevance
“…This requires consideration of the decision rule used in the same/different task. In a series of experiments, we examined repetition priming for the word matching task employed in Experiment 3 (Davelaar, Huber, Tian, & Weidemann, submitted). In different conditions, either the cue word or the target word repeated a word from the last trial.…”
Section: Discussionmentioning
confidence: 99%
“…This requires consideration of the decision rule used in the same/different task. In a series of experiments, we examined repetition priming for the word matching task employed in Experiment 3 (Davelaar, Huber, Tian, & Weidemann, submitted). In different conditions, either the cue word or the target word repeated a word from the last trial.…”
Section: Discussionmentioning
confidence: 99%
“…This technique allows the assessment of spatial similarity in electrophysiological studies regardless of response magnitude and estimates the similarities in underlying neural sources distribution (e.g., Luo, Tian, Song, Zhou, & Poeppel, 2013; Tian & Huber, 2013; Tian & Poeppel, 2010, 2013; Davelaar, Tian, Weidemann, & Huber, 2011; Huber, Tian, Curran, O'Reilly, & Woroch, 2008). In this method, each topographical pattern is considered as a high-dimensional vector, where the number of dimensions equals the number of sensors in recording.…”
Section: Methodsmentioning
confidence: 99%
“…Most importantly, a growing number of studies have found these techniques to be reliable and useful (e.g., [2, 25, 26]).…”
Section: Discussionmentioning
confidence: 99%